Dual αV-integrin and neuropilin-1 targeting peptide CEND-1 plus nab-paclitaxel and gemcitabine for the treatment of metastatic pancreatic ductal adenocarcinoma: a first-in-human, open-label, multicentre, phase 1 study. (October 2022) - Dean, Andrew; Gill, Sanjeev; McGregor, Mark; Broadbridge, Vy; Järveläinen, Harri A; Price, Timothy
Summary: Background: CEND-1 is a novel cyclic peptide that targets αV integrins and neuropilin-1 and enhances tumour delivery of co-administered anticancer drugs. We investigated the safety, tolerability, and biological activity of CEND-1 in patients with metastatic pancreatic ductal adenocarcinoma in combination with nab-paclitaxel and gemcitabine. Methods: This open-label, multicentre, phase 1 study, conducted at three hospitals in Australia, enrolled participants aged 18 years or older with histologically confirmed metastatic pancreatic ductal adenocarcinoma who had one or more lesions measurable on MRI or CT, an Eastern Cooperative Oncology Group performance status score of 0 or 1, and a life expectancy of at least 3 months. Exclusion criteria included previous chemotherapy and brain metastases or other malignancy (unless receiving curative intent). There was no randomisation or masking. CEND-1 monotherapy was given as an intravenous fluid bolus on day 1 of a run-in phase of 7 days (0·2–3·2 mg/kg) followed by CEND-1 plus intravenous gemcitabine (1000 mg/m 2 ) and nab-paclitaxel (125 mg/m 2 ) on days 1, 8, and 15 of 28-day treatment cycles until disease progression. The primary safety endpoints were incidence, severity, and duration of treatment-emergent and treatment-related adverse events; overall survival; and clinical laboratory results, which were all assessed in the safety population. This study is registered with ClinicalTrials.gov, NCT03517176, and the Australian New Zealand Clinical Trials Registry, ACTRN12618000804280. Findings: Between Aug 13, 2018, and Nov 30, 2019, 31 patients were enrolled (eight in the dose-escalation phase [cohort 1a] and 23 in the expansion phase [cohort 1b]). Two patients were excluded from the efficacy population. No CEND-1 dose-limiting toxicities were observed in the safety population (n=31). The most common grade 3 or 4 events were neutropenia (17 [55%] patients), anaemia (eight [26%]), leukopenia (five [16%]), and pulmonary embolism (four [13%]). Serious adverse events occurred in 22 (71%) patients, mostly related to disease progression. Ten deaths occurred during the study due to progression of metastatic pancreatic cancer (n=9) and a left middle cerebral artery stroke (n=1). In the efficacy population (n=29), 17 (59%) patients had an objective response, including one complete response and 16 partial responses. After a median follow-up of 26 months (IQR 24–30), median overall survival was 13·2 months (95% CI 9·7–22·5). Interpretation: CEND-1 with nab-paclitaxel and gemcitabine has an acceptable safety profile, with no dose-limiting toxicities and encouraging activity. Adverse events were generally consistent with those seen with nab-paclitaxel and gemcitabine. Further randomised trials to determine the efficacy of CEND-1 are warranted. Funding: DrugCendR Australia Pty.